Upaya Kepala Sekolah dalam Meningkatkan Kepuasan Kerja Guru di SMAN 4 Kota Jambi - Suryadi, Suryadi; Nopriansyah, Ahmad; Bahri, Zul; Muspawi, Mohamad; Rahman, K.A. (UMSU, 2024)
This research aims to examine how the principal at SMA Negeri 4 Jambi City tries to increase teacher job satisfaction. This research was motivated by the low job satisfaction of teachers at the school, which can be seen from a lack of appreciation, low motivation and poor communication. This problem causes teachers to feel apathetic towards their responsibilities, often complain, and are dissatisfied with the support provided by the school. This study used qualitative research methods. To collect data for this research, the author conducted interviews, made observations, and collected documentation. The key informant for this research is the teacher at SMA Negeri 4 Jambi City, while the school principal acts as a supporting informant. Based on information gathered from several respondents, it appears that school principals play a very positive and influential role in school organizations. The principal has made significant efforts to improve school performance by providing exceptional services, thereby aiming to increase teacher satisfaction.